Effect of inoculation of Tarwi plants with Bradyrhizobium spp. strains isolated from a wild lupine, under greenhouse conditions - Taco-Taype, Nataly (2020)
The “tarwi" or "chocho” (Lupinus mutabilis Sweet) is the unique specie of the genus Lupinus cultivated in America, appreciated for its high protein content in seeds, and the ability to fix nitrogen in symbiotic association with rhizobia. Its genetic variability is reinforced by approximately 84 wild species in Peru. The present investigation was carried out to show if the rhizobia of a wild lupino (Lupinus sp.) might be able to nodulate and promote the growth of tarwi. The root nodules were collected from an abandoned crop field of Huaraz (Ancash-Peru) at 3497 m of altitude, were isolated 8 slow-growing (6-7 days) rhizobial strains, which due to their microbiological and molecular characteristics correspond to the genus Bradyrhizobium. These strains were inoculated in tarwi seeds, and co-inoculated to the 15-day seedlings. It was applied a completely randomized design with 11 treatments (including the control strain LMRT28, N+ with nitrogen fertilization and N- without fertilization) and 5 repetitions. After 70 days of growth in greenhouse conditions, all treatments with native strains, with the exception of LSHZ-L1 and LSHZ-L2, showed reddish-colored root nodules, indicator of leghemoglobin activity. Six of the strains significantly increased the aerial length of the plants respect to the N- and the LMRT28 treatment; also, there were significant differences in relation of aerial dry weight being better in five treatments with native strains. The major foliar coverage was developed by LSHZ-L7; and the greatest number of secondary nodules was showed in LSHZ-L3, which is correlated with the dry weight of the root.